Intercomparison of non-LTE radiative transfer codes - Von Clarmann, T; Linden, A; Funke, B; Dudhia, A; Edwards, D; Lopez-Puertas, M; Kerridge, B; Kostsov, V; Timofeyev, Y (2001)
Limb infrared spectra calculated by the KOPRA, GENLN2, RFM, and SPIRT radiative transfer algorithms were intercompared with special emphasis on non-local thermodynamic equilibrium emission. The overall agreement is usually better than approximately 0.5 percent except for single phenomena which have been assessed in more detail. Most spectral radiance discrepancies occur also under local thermodynamic equilibrium conditions and are attributed to different treatment of far wings of lines, integration schemes and mass-weighted averaging of atmospheric state temperature and pressure along slant path segments, as well as different spectral sampling during the calculation of monochromatic radiances. Additional differences in the non-local thermodynamic equilibrium case are presumably due to the different treatment of inhomogeneities of vibrational temperatures with height during numeric integration of radiative transfer.